Penerapan Model Multi-Product Newsvendor Problem Untuk Memaksimalkan Ekspektasi Keuntungan Toko Roti X - Fran Setiawan (Universitas Katolik Parahyangan, 2021)
Bakery shop X sells its products using its car which operate in Bandung District area. The problem which faced by bakery shop X is the high percentage of leftover bread that is not sold out. Although some of breads can be resold, there has been a drastic decline in the appearance and the quality of the leftover breads. Bread which has a diminishing value in appearance and quality is sold with the lower price which result in decrease in profit. This research using multi-product newsvendor problem to determine how much every kind of breads must be produced in each day so that the profit expectation can be maximized and will indirectly minimize the amount of remaining breads. This research will applied that the bread which allowed to sold is the bread which produced in 1 day so that the customer do not get the unfresh bread. The result of the implementation of the model through simulation shows a decrease in the percentage of leftover bread in the majority of breads based on the demand data of 1 week and higher profit expectations are obtained.